2014
DOI: 10.1016/j.nicl.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Acute neuropharmacological effects of atomoxetine on inhibitory control in ADHD children: A fNIRS study

Abstract: The object of the current study is to explore the neural substrate for effects of atomoxetine (ATX) on inhibitory control in school-aged children with attention deficit hyperactivity disorder (ADHD) using functional near-infrared spectroscopy (fNIRS). We monitored the oxy-hemoglobin signal changes of sixteen ADHD children (6–14 years old) performing a go/no-go task before and 1.5 h after ATX or placebo administration, in a randomized, double-blind, placebo-controlled, crossover design. Sixteen age- and gender-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 112 publications
9
69
1
Order By: Relevance
“…We could conclude that, when taken together, the current fNIRS results illustrate the specific neuropharmacological mechanism of ATX underlying the functional normalization of the attention network components. Furthermore, these results extend the conclusions of our previous fNIRS studies revealing ATX-and MPH-induced normalization in the right MFG/ IFG: 25,26,28 fNIRS-based measurement can distinguish between neural substrates of the DA and NA systems differentially involved in inhibitory and attentional controls.…”
Section: Fnirs Examination Of Oddball Task and Atx Effectssupporting
confidence: 88%
See 3 more Smart Citations
“…We could conclude that, when taken together, the current fNIRS results illustrate the specific neuropharmacological mechanism of ATX underlying the functional normalization of the attention network components. Furthermore, these results extend the conclusions of our previous fNIRS studies revealing ATX-and MPH-induced normalization in the right MFG/ IFG: 25,26,28 fNIRS-based measurement can distinguish between neural substrates of the DA and NA systems differentially involved in inhibitory and attentional controls.…”
Section: Fnirs Examination Of Oddball Task and Atx Effectssupporting
confidence: 88%
“…On the other hand, in post-MPH and ATX administration ADHD groups, functional normalization was observed, using fNIRS, in the right MFG/IFG during go/no-go tasks. 25,26,28 These activation patterns were consistent with the results of previous fMRI studies. 33,34 In essence, the right prefrontal dysfunction in ADHD children was normalized by MPH for both inhibitory and attentional controls, and by ATX for inhibitory control.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…These studies have revealed hypoactivation in the right frontal lobe including the prefrontal cortex (PFC; Xiao et al, 2012; Yasumura et al, 2014), middle frontal gyrus (MFG), and inferior frontal gyrus (IFG) (Monden et al, 2012, 2015; Nagashima et al, 2014a,b,c), presumably because NIRS probes can easily be applied to the frontal region (see Table 1). These studies also found hypoactivation in the temporal (Ichikawa et al, 2014; Köchel et al, 2015) and parietal cortices (Nagashima et al, 2014b) as well.…”
Section: Lateralization In Atypical Neural Function In Adhdmentioning
confidence: 99%